Farm size, technology adoption and agricultural trade reform: Evidence from Canada - W. Mark Brown; Shon Ferguson; Crina Viju (Research Institute of Industrial Economics (IFN), 2018)
Using detailed census data covering over 40,000 farms in Alberta, Saskatchewan and Manitoba, Canada, we document the vast and increasing farm size heterogeneity, and analyze the role of farm size in adapting to the removal of an export subsidy in 1995. We find that larger farms were more likely to switch to new labor-saving tillage technologies in response to the large negative shock to grain prices caused by the reform. Small- and medium-sized farms responded to the reform by adopting the more affordable minimum tillage technology. We develop a simple model of heterogeneous farms and technology adoption that can explain our findings. The results suggest that farm size plays a crucial role in determining farm-level adaptation to agricultural trade reform. Consistent with the Alchian-Allen hypothesis, the increase in per-unit trade costs due to the reform was associated with farms shifting their production of crops from low-value wheat to higher value canola.
Keywords: F14; O13; Q16; Q17; Q18; 330; Agricultural Trade Liberalization; Export Subsidy; Technical Change; Farm Size; Firm Heterogeneity